Integration of UTAUT model in context to Zigzag technology adoption in brick kilns of Punjab (Journal of Pharmaceutical Negative Results, 2023)
Due to the increase in diseases and environmental pollution, nowadays everyone's attention is towards controlling pollution. Industries are mainly liable for increasing environment pollution. In Punjab there are around 3000 brick kilns, out which many kilns are using old type technology, while to control pollution there is option available in the form of Zigzag kiln. This technology is very helpful in reducing pollution and reducing usage of coal. Study aims to identify factors of Zig-zag technology adoption using Unified Theory of Acceptance and Use of Technology (UTAUT). For sampling the 340 brick kiln owners from 22 districts in the Indian region of Punjab served as the sample for this study, which was based on cross-sectional data. Data was collected from assigning authorities of brick kilns using structured questionnaires.Zig-zag technology in brick kilns of Punjab has a remarkable impact on productivity, but impact of social influence on behavior intention is found to be pointless. Effort Expectancy (EE), Performance expectancy (PE) and Facility Conditions (FC) are revealed to have a significant impact on adoption of Zig-zag klin technology.